2018
DOI: 10.1002/adfm.201705512
|View full text |Cite
|
Sign up to set email alerts
|

Ultrathin Lutetium Oxide Film as an Epitaxial Hole‐Blocking Layer for Crystalline Bismuth Vanadate Water Splitting Photoanodes

Abstract: Here a novel ultrathin lutetium oxide (Lu 2 O 3 ) interlayer is integrated with crystalline bismuth vanadate (BiVO 4 ) thin film photoanodes to facilitate carrier transport through atomic-scale interface control. The epitaxial Lu 2 O 3 interlayer fabricated by pulsed laser deposition features very few structural defects at the back contact of the heterojunction, and forms a unique band alignment that favors photohole blocking. An optimized interlayer thickness of 1.4 nm significantly enhances charge separation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 38 publications
2
32
0
Order By: Relevance
“…In general, the establishment of epitaxial thin film photoelectrode has been widely recognized to maximize the potential of photoelectrode materials in pursuit of a further breakthrough by exploring its fundamental properties. For that reason, recently, various research on the growth of the epitaxial BiVO 4 have been reported, to explore its fundamental properties for PEC water splitting [13,19,[56][57][58][59][60][61][62][63]. Based on many theoretical predictions, the research related to the growth of the epitaxial monoclinic BiVO 4 (a = 5.1956 Å, b = 5.0935 Å, c = 11.6972 Å, β = 90.387 • ) films have been focused on growth along the c-axis.…”
Section: Application Of Facet Engineering In Pec Water Splittingmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the establishment of epitaxial thin film photoelectrode has been widely recognized to maximize the potential of photoelectrode materials in pursuit of a further breakthrough by exploring its fundamental properties. For that reason, recently, various research on the growth of the epitaxial BiVO 4 have been reported, to explore its fundamental properties for PEC water splitting [13,19,[56][57][58][59][60][61][62][63]. Based on many theoretical predictions, the research related to the growth of the epitaxial monoclinic BiVO 4 (a = 5.1956 Å, b = 5.0935 Å, c = 11.6972 Å, β = 90.387 • ) films have been focused on growth along the c-axis.…”
Section: Application Of Facet Engineering In Pec Water Splittingmentioning
confidence: 99%
“…The growth of epitaxial BiVO 4 (001) thin films also could be achieved on the SrTiO 3 (001) (STO, a = 3.905 Å) substrate by the insertion of the WO 3 as template layer, which could reduce the lattice mismatch between the BiVO 4 and the STO [13]. In addition, Zhang et al reported on the improved PEC performance of the epitaxial BiVO 4 (001) thin film by inserting lutetium oxide (Lu 2 O 3 ) as a hole blocking layer [60].…”
Section: Application Of Facet Engineering In Pec Water Splittingmentioning
confidence: 99%
“…Among these methods, BiVO 4 doping, photocharging, cathodic polarization, nanostructuring,, as well as its interfacing with: highly active OER co‐catalysts ( cocats ) another SC and plasmonic materials, have shown great promise. The synthesis of photoelectrochemically active BiVO 4 on a conductive substrate is thus of great importance and can be performed by: i ) spray‐based,,, or ii ) hydrothermal, methods, iii ) metal‐organic decomposition,,, iv ) physical vapor deposition, and v ) electrodeposition ,. The latter approach is very attractive due to its simplicity and its low cost, and electrodeposited BiVO 4 has already led to very important breakthroughs ,.…”
Section: Figurementioning
confidence: 99%
“…For n‐type materials like BiVO 4 , the underlayer is sometimes called a hole blocking layer or a “hole mirror.” Previous works have commonly utilized tin oxide (SnO 2 ) and tungsten oxide (WO 3 ), where SnO 2 is perhaps the most studied underlayer material for BiVO 4 . Other materials that have been used as interfacial layers in BiVO 4 photoanodes include TiO 2 , Lu 2 O 3 , and GaO x N 1‐ x ; SnO 2 was selected for this study based on its suitable band alignment relative to BiVO 4 , stability, low cost, and as‐yet unexplored investigation as a BiVO 4 underlayer using atomic layer deposition (ALD). Popular synthetic methods for SnO 2 , such as spray pyrolysis, yield optimal PEC performance with 65–80 nm of underlayer thickness .…”
Section: Introductionmentioning
confidence: 99%